Gambaran Stres Akademik Siswa SMA Negeri Selama Pembelajaran Jarak Jauh (PJJ) - Livia Safira; Maria Theresia Sri Hartati (Empati-Jurnal Bimbingan dan Konseling, 2021)
Abstract. Academic stress is a problem that is felt by every students. E-learning based distance learning often causes the emergence of new stressors in learning, such as internet connection, understanding of material, and various problems with assignments and daily tests. The purpose of this study was to describe the academic stress of high school students while carrying out distance learning (PJJ). Collecting data using an Academic Stress scale that has been tested for validity and reliability. This research is a descriptive quantitative type with a sample of 311 students from two high schools, namely SMA Negeri 04 Semarang and SMA Negeri 09 Semarang. The results showed that the majority of students experienced moderate academic stress (M = 2.78) during distance learning.Abstrak. Stres akademik merupakan suatu permasalahan dirasakan setiap pelajar. Pembelajaran jarak jauh berbasis e-learning tak jarang meyebabkan munculnya stressor baru dalam belajar, seperti koneksi internet, pemahaman materi, dan berbagai permasalahan tugas serta ulangan harian. Tujuan dari penelitian ini ialah untuk mengetahui gambaran stres akademik siswa SMA selama melaksanakan pembelajaran jarak jauh (PJJ). Pengumpulan data menggunakan skala Stres Akademik yang sudah diuji validitas dan reliabilitasnya. Penelitian ini berjenis kuantitatif deskriptif dengan sampel sebanyak 311 siswa dari dua SMA, yakni SMA Negeri 04 Semarang dan SMA Negeri 09 Semarang. Hasil penelitian menunjukan mayoritas siswa mengalami stres akademik tingkat sedang (M= 2,78) selama pembelajaran jarak jauh.